2003
DOI: 10.1021/jm030781p
|View full text |Cite
|
Sign up to set email alerts
|

Docking and Database Screening Reveal New Classes ofPlasmodiumfalciparumDihydrofolate Reductase Inhibitors

Abstract: Plasmodium falciparum dihydrofolate reductase (PfDHFR) is an important target for antimalarial chemotherapy. Unfortunately, the emergence of resistant parasites has significantly reduced the efficiency of classical antifolate drugs such as cycloguanil and pyrimethamine. In this study, an approach toward molecular docking of the structures contained in the Available Chemicals Directory (ACD) database to search for novel inhibitors of PfDHFR is described. Instead of docking the whole ACD database, specific 3D ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 50 publications
2
83
0
Order By: Relevance
“…As described in previous sections, the identified hits show all the necessary interactions in the active site which are required by antifolate PfDHFR inhibitors for effective inhibition of this enzyme 6,7,11,18,25 . Their hydrogen bond donor features interact with Asp54 and Ile14 or/and Leu164, whereas the hydrophobic portions interact with amino acid residues Met55, Ser111, Pro113, and other amino acids via hydrophobic interactions.…”
Section: Binding Modes (Interactions) Of the Identified Hitsmentioning
confidence: 81%
See 3 more Smart Citations
“…As described in previous sections, the identified hits show all the necessary interactions in the active site which are required by antifolate PfDHFR inhibitors for effective inhibition of this enzyme 6,7,11,18,25 . Their hydrogen bond donor features interact with Asp54 and Ile14 or/and Leu164, whereas the hydrophobic portions interact with amino acid residues Met55, Ser111, Pro113, and other amino acids via hydrophobic interactions.…”
Section: Binding Modes (Interactions) Of the Identified Hitsmentioning
confidence: 81%
“…The hits were selected based on their docking scores, binding orientations, and interactions with key amino acid residues in the active site (Asp54, Ile14, and Leu164) as well as their interactions in the hydrophobic region of the active site. Because of the flexible nature of their side chains, there are no potential steric clashes with Asn108, which is known to be responsible for resistance of the mutant parasite to antimalarial drugs 1 and 2 6,7,[10][11][12][13]18,25 . The hits also fulfill all the properties required by drug-like molecules 47,48 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is frequently used to minimize the size of a chemical library before a high throughput screen (HTS). Even if industrial experience with novel targets is seldom reported, many case studies relate successful uses of such methods [7,8]. For the subsequent step in the drug-discovery process, i. e. hit / lead optimization, there are fewer reports [9].…”
Section: Introductionmentioning
confidence: 99%